Analisis Representase Maskulinitas Dalam Iklan Kopi Luwak Sin Tae Yong - Ayu Wardani, Ayu Wardani; Surya Ade Pratama; Hasan Sazali (Jurnal Riset Rumpun Seni, Desain dan Media, 2023)
Shin Tae Yong is a man from South Korea where he is the soccer coach for the Indonesian National Team. He became famous since becoming a coach because he won the match between Indonesia and Malaysia with a score of 4-1. Since then, he has been partnered with by many big brands to be used as an advertising model. Kopi Luwak advertisement is one of the brands that made Shin Tae-yong an advertising model. The purpose of this research is to analyze how Shin Tae-yong's masculinity is portrayed in Luwak coffee advertisements. The research method used in this study is the semiotic analysis method of Roland Barthes. According to Roland Barthes, there are three cores of semiotics, namely denotative, connotative and myth. The results of this study found that several advertisements, such as the scene of drinking coffee before playing football.